A field manual for palliative care in humanitarian crises - Waldman, Elisha; Glass, Marcia (New York, NY : Oxford University Press, 2019)
As humanitarian aid organizations have evolved, there is a growing recognition that incorporating palliative care into aid efforts is an essential part of providing the best care possible. This text educates and provides guidance for clinicians not formally trained in palliative care in how to incorporate its principles into their work in crisis situations. Written by a team of international experts, this pocket-sized manual identifies the needs of people affected by natural hazards, political or ethnic conflict, epidemics of life-threatening infections, and other humanitarian crises.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 30, 2019).
Keywords: Palliative treatment; Medical assistance